Strategies To Increase Customer Satisfaction Through Relationship Marketing And Discounts At Penyet Kalasan Chicken Restaurant - Loo, Petrus; Gultom, Pesta; Luckyanto, Marvin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study investigates the influence of relationship marketing and discounts on customer satisfaction at the Penyet Kalasan Chicken Restaurant. The study adopts a quantitative approach with sampling determined using the Hair formula. Data were analyzed through multiple linear regression. The results show that relationship marketing has a significant positive effect on customer satisfaction, with a regression coefficient of 0.714 and tcount (10.054) greater than ttable (1.9804), and a significance value below 0.05. Similarly, discounts also exert a significant positive effect, indicated by a regression coefficient of 0.251 and tcount (3.278) > ttable (1.9804). The joint effect of both variables is confirmed by the F-test, where Fcount (89.698) exceeds Ftable (3.07), suggesting that relationship marketing and discounts simultaneously influence customer satisfaction. Furthermore, the coefficient of determination (R²) indicates that 60.5% of the variance in customer satisfaction is explained by these two variables, while 39.5% is attributed to other factors outside the study. These findings emphasize that customer relationship strategies and discount programs are critical drivers of satisfaction in the restaurant industry. Therefore, managers are advised to strengthen relational engagement with customers while offering attractive promotional pricing to sustain loyalty and competitiveness in a highly dynamic market.